A humanização na saúde como instância libertadora The humanization in health as a freedom instance - Alberto Olavo Advincula Reis; Isabel Victoria Marazina; Paulo Rogério Gallo (Universidade de São Paulo, 2004)
O texto discute a política de Humanização em Saúde do ponto de vista da lógica que a sustenta, em particular como uma ação da singularidade dos atores implicados no processo de produção da Saúde. A análise desenvolvida aponta para o fato de que as práticas de atenção à saúde, quando de acordo com os cânones da lógica utilitária, refletem não apenas uma ordem autoritária, como produzem sujeitos cerceados, fragmentados e incapazes. A humanização em Saúde é considerada uma possibilidade política de se alterar essa lógica e de instaurar, no interior das instituições, espaços de liberdade capazes de acolher, amparar, sustentar e dar significado à presença e às ações de profissionais de saúde, gestores e pacientes, ao considerar suas dimensões subjetivas e singulares. The text presents the politics of Humanization in Health from the point of view of the logic that gives support to it, i.e., as an action of the actors' singularity implicated in the process of Health production. The analysis points to the fact that the practices devoted to health attention, when in consonance with the prescriptions of the utilitarian logic reflect an authoritarian order, but also produce reduced, fragmented and incapacitated subjects. The humanization in the field of Health is considered as a political possibility of altering that logic and of establishing within the institutions spaces of freedom capable to hold, to aid, to sustain and to give a different meaning to the presence and professionals providing health actions, as well as managers and patients, considering their subjective and singular dimensions.